Debt Management Performance Assessment : Guinea - World Bank (World Bank, Washington, DC, 2020)
The DeMPA methodology provides a comprehensive set of indicators spanning the full range of DeM functions and used for in-depth analysis of the quality of government debt management functions and institutions. The results of the DeMPA evaluation help the central government authority to take stock of the current DeM situation, assess quality of undertaken reforms and design medium term reforms’ plan. The Guinean economy is recovering well from two recent major shocks: the Ebola epidemic in 2014-2015 and a decline in commodity prices after 2015. After slowing in 2014–2015 to an average of 3.6 percent, growth reached 10.4 percent in 2016, supported by a recovery in mining, good agricultural performance, and more reliable electricity supply. The mining sector accounted for more than half the growth rate, supported by the expansion of bauxite and alumina production and increased demand. The growth momentum is expected to continue with real growth reaching 5.8 percent in 2018 and averaging approximately 5 ½ percent over the medium term, driven by strong performance in mining, construction, and scaled-up investments in infrastructure. Risks to these projections are balanced, with downside potential from socio-political tensions, delays in projects and reform implementation, and upside potential from faster-than-expected mining production capacity coming on stream.